PWE-109 Measurement of Infliximab and Anti-Infliximab Antibodies - Analytical Aspects and Clinical Implications. (4th June 2013) - Unsworth, N; Arkir, Z; Irving, P; Ward, M G; Richards, G
Abstract : Introduction: Commercial assays for monitoring Infliximab (IFX) and anti-drug antibodies (ADAb) are currently available. The heterogeneity of these assays and lack of standardisation of ADAb may cause difficulties in interpretation, in particular comparing bridging ELISA and radioimmunoassay (RIA). Bridging ELISAs have high specificity but are more prone to inhibition by drug hence may underestimate ADAb, whereas false positive results can be seen with RIA. Aims Evaluation of (i) the effect of common interferents in the LISA-Tracker Premium ELISA assay (Theradiag). (ii) the inhibitory effect of IFX on the detection of ADAb. Methods: The LISA-Tracker kit was used for the quantitative determination of free drug and ADAb by indirect and bridging assay principles respectively. The measurement range was 0.1 to 5 μg/mL for IFX and 10 to 200 ng/mL for ADAb (> 10 ng/mL considered positive). Interference studies were carried out using samples with known levels of haemolysis, icterus, rheumatoid factor (RF) and paraprotein (IgG kappa = 17 g/L). All patients had no history of exposure to biologics. Samples were run neat and diluted with samples of known IFX and ADAb concentration to assess recovery. Samples with known levels of ADAb were spiked with aqueous solutions of IFX (2.4, 1.2 and 0.3 µg/mL) at a ratio of 1:2. Predicted ADAb concentrations were calculated by sample dilution in drug-free diluent. Results: No interference was observed from haemolysis (up to 0.6 g/dL haemoglobin equivalent), icterus (up to 349 μmol/L bilirubin), RF (up to 885 U/mL) and paraprotein as confirmed by recoveries of 93–113% for drug and ADAb. Spiking experiments The inhibitory effect of IFX on ADAb detection was observed in both low and high level ADAb samples with ADAb only detectable in sample 2 i.e. as free, not complex form. Comparing expected with measured concentrations of IFX in the spiked samples indicated a difference in recovery between the low and high ADAb positive samples suggesting decreased availability of free IFX in the presence of ADAb. Conclusion: This study shows that the LISA-Tracker kit is not affected by tested interferents. Results from spiking experiments highlight the importance of measuring trough levels and also indicate that the presence of ADAb (detectable or undetectable) can limit the availability of free IFX, leading to sub-therapeutic levels. LISA-Tracker is a simple, robust assay which has been implemented in our hospital and is routinely used as a personalised approach to prescribing and optimising anti-TNFα therapies in IBD. Disclosure of Interest: None Declared.